Callus Formation Process on Rubber Plant Shoot Explants (Hevea Brasiliensis Muell. Arg.) with Ms Medium - Dwi Sucianingtyas Sukamto (PROGRAM STUDI PENDIDIKAN BIOLOGI, 2021)
Rubber Plant (Hevea brasiliensis Muell Arg) is one of the plantation commodities that is important due to its role as the income source, boosting the economic growth around rubber plant area, open job opportunities, foreign exchange source as well as related to environmental conservation of biological resources. Propagation of rubber plant (Hevea brasiliensis Muell Arg) are currently still using conventional method, namely grafting. This research aims to determine the process of callus formation in a combination of different NAA and BAP concentrations. The research design uses research type observation with cross sectional type (cross sectional design). Media that is used i.e. MS with BAP and NAA combination concentration, that is: control (MS0) (P1); BAP 1.5 mg/L + NAA 0.05 mg/L (P2), BAP 2 mg/L + NAA 0.1 mg/L (P3), BAP 2.5 mg/L + NAA 0.2 mg/L (P4). Each treatment was repeated six times. The parameters observed were callus formation process for 3 weeks. Based on the results of data analysis shows that the process of callus formation begins with swelling of explants starting the first week, the second week changes color to greenish yellow and third week callus is formed in BAP treatment 1.5 mg / L + NAA 0.05 mg / L (P2) .